Production and characterization of spray-dried swamp eel (Monopterus albus) protein hydrolysate prepared by papain - Sri Priatni,; Harimadi, Kezia; Buana, Efendi; Kosasih, Wawan; Rohmatussolihat Rohmatussolihat, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Protein hydrolysate from swamp eel (Monopterus albus) has been prepared by enzymatic hydrolysis process using papain enzyme. Evaluation of the extent of protein hydrolysis was conducted by measuring the degree of hydrolysis (DH). The optimization of protein hydrolysate production has been carried out by analyzing the influences of papain enzyme concentration, temperature, and time of hydrolysis on the degree of hydrolysis (DH) using RSM design. The optimized product was spray-dried and analyzed the proximate (moisture, lipid, protein) content and the yield (%). The fish protein hydrolysate (FPH) powder product was characterized by the foaming capacity and stability, and also by FTIR, DSC and PSA methods. The optimum condition of enzymatic hydrolysis of swamp eel protein was obtained by an addition 0.49 % of papain enzyme at 45 oC for 9 hours. The degree of hydrolysis (DH) of this product was 7.96 % with a yield of 14.72 %. The foaming capacity of swamp eel protein hydrolysate powder was between 12.5 - 62.5 % and the foaming stability was between 3.22 - 31.25 %. The highest foaming capacity and stability of this product was reached at pH 4.0. Based on the spectrum FTIR analysis, the FPH product contained amines, aromatics, aliphatics, amide B and amide II groups. DSC analysis of the FPH product showed two peaks (Tm) at 65 oC and 108.5 oC. The particle size of the FPH powder product was distributed within 100 nm-1500 nm range with the highest intensity was 8.91 %. This study shows the potential usage of swamp eel for the production of FPH by enzymatic hydrolysis using papain enzyme with high yield and serves as a protein supplement.